(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Natural regeneration of tree species is the major means of understanding the restoration potentiality of a secondary forest. Natural regeneration of a forest is a tool for measuring the health of the forest ecosystem. Natural regeneration status of tree species in Hazarikhil Wildlife Sanctuary (HWS) in Chittagong North Forest Division, Bangladesh was assessed laying 75 systematic quadrats of 4m×4m in size. A total of 90 regenerating tree species belonging to 34 families was identified from the HWS. Euphorbiaceae family possessed maximum regenerating tree species (14 species) followed by Mimosaceae (7), Lauraceae and Meliaceae (6 species each), and Moraceae (5 species). The overall seedling density was 7,083 per ha where Ficus hispida showed the highest number of seedlings (792 per ha) followed by Quercus sp. (475), Ficus religiosa (408), Lithocarpus elegans (375) and Lepisanthes rubiginosa (367). The number of Ficus hispida seedlings per ha was higher due to high coppicing ability. Lepisanthes rubiginosa attained maximum IVI (27.59) followed by Ficus hispida (21.18) and Quercus oxyodon (13.32). The seedlings of Aegle marmelos, Lithocarpus sp., Flacourtia jangomas, Albizia odoratissima, Acronychia padunculata, Chaetocarpus castanicarpus, Maesa paniculata, Crypteronia paniculata, Streblus asper and Mussaenda roxburghii were also found common in the study area. The findings will create baseline information of regenerating tree species, composition, diversity and population structure which can be used for monitoring future changes as well as taking policy decisions for the management of this Wildlife Sanctuary. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 1-12